PrsA2 (CD630_35000) of Clostridioides difficile Is an Active Parvulin-Type PPIase and a Virulence Modulator - Ünal, Can Murat; Berges, Mareike; Smit, Nathiana; Schiene-Fischer, Cordelia; Priebe, Christina; Strowig, Till; Jahn, Dieter; Steinert, Michael (Frontiers in Microbiology, 2018)
Clostridioides difficile is the main cause for nosocomial antibiotic associated diarrhea and has become a major burden for the health care systems of industrial countries. Its main virulence factors, the small GTPase glycosylating toxins TcdA and TcdB, are extensively studied. In contrast, the contribution of other factors to development and progression of C. difficile infection (CDI) are only insufficiently understood. Many bacterial peptidyl-prolyl-cis/trans-isomerases (PPIases) have been described in the context of virulence. Among them are the parvulin-type PrsA-like PPIases of Gram-positive bacteria. On this basis, we identified CD630_35000 as the PrsA2 homolog in C. difficile and conducted its enzymatic and phenotypic characterization in order to assess its involvement during C. difficile infection. For this purpose, wild type CdPrsA2 and mutant variants carrying amino acid exchanges mainly in the PPIase domain were recombinantly produced. Recombinant CdPrsA2 showed PPIase activity towards the substrate peptide Ala-Xaa-Pro-Phe with a preference for positively charged amino acids preceding the proline residue. Mutation of conserved residues in its active site pocket impaired the enzymatic activity. A PrsA2 deficient mutant was generated in the C. difficile 630Δerm background using the ClosTron technology. Inactivation of prsA2 resulted in a reduced germination rate in response to taurocholic acid, and in a slight increase in resistance to the secondary bile acids LCA and DCA. Interestingly, in the absence of PrsA2 colonization of mice by C. difficile 630 was significantly reduced. We concluded, that CdPrsA2 is an active PPIase that acts as a virulence modulator by influencing crucial processes like sporulation, germination and bile acid resistance resulting in attenuated mice colonization.